Domesticating the Geopolitical: Rethinking Popular Geopolitics through Play. Issue 5 (19th October 2020) - Woodyer, Tara; Carter, Sean
ABSTRACT: In this paper, we take the emergence of the Her Majesty's Armed Forces toy range in 2009 as a starting point for thinking through the domestication of geopolitics through practices of play. Empirically, the paper draws upon substantive, innovative and original research undertaken with children in their homes, via a series of play ethnographies; conceptually, the paper draws upon the notion of 'domestication' and argues that ideas from these literatures might be usefully adopted as a means of reconfiguring popular geopolitics. In so doing, we argue not only that toys, games and play warrant much greater attention as forms of popular geopolitics, but also that the idea of domestication has much to offer wider conceptions and framings around popular geopolitics itself. The paper thus advances claims for a significant reformulation of popular geopolitics as an encounter between texts, objects, bodies and practices. More specifically, the rich ambiguity of the observed practices emerging from our play-centred ethnographic approach speaks clearly to the need to avoid prioritising the public over the private, cultural producers over audience, and the discursive over the affective in our theorisations of domestication. While we should be attentive to the highly orchestrated practices of anticipating domesticity and the multiple sites of geographical production assembled though these practices, we should not ignore the excess inherent within the incomplete, experimental process of domestication.